Essentials of supply chain management - Hugos, Michael H. (Essentials series., 2018)
"The bestselling guide to the field, updated with the latest innovations Essentials of Supply Chain Management is the definitive guide to the field, providing both broad coverage and necessary detail from a practical, real-world perspective. From clear explanation of fundamental concepts to insightful discussion of supply chain innovation, this book offers students and professionals a comprehensive introduction with immediately-applicable understanding. The fourth edition has been updated to reflect the current state of the field, with coverage of the latest technologies and new case studies that illustrate critical concepts in action. Organized for easy navigation and ease-of-use, this invaluable guide also serves as a quick reference for managers in the field seeking tips and techniques for maximizing efficiency and turning the supply chain into a source of competitive advantage. The supply chain underpins the entire structure of manufacturing and retailing. Well-run, it can help a company become a global behemoth or, if poorly-managed, it can sink a company before the product ever sees the light of day. The supply chain involves many moving parts, constantly-changing variables, and a network of other business that may have different priorities and interests keeping it all running smoothly is a complex, but immensely powerful skill. This book takes you inside the supply chain to show you what you need to know. Understand the fundamental concepts behind supply chain management Learn how supply chains work, and how to measure their performance Explore the ways in which innovation is improving supply chains around the world Examine the supply chain as a source of competitive advantage Whether you're at the front or the back of your supply chain, your business is affected by every other company and event in the chain. Deep understanding and a host of practical skills are required to accurately predict, react to, and manage the ever-changing stream of events that could potentially disrupt the flow. Essentials of Supply Chain Management prepares you to take on the challenge and succeed."--